BIM Based Facility Condition Assessment - Faqih, Faisal; Zayed, Tarek; Soliman, Ehab (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Current practices of using traditional methods of managing data using spreadsheets or hard paper copies for various building data, are commonly being used during building inspection and condition assessment. Building Information Modelling (BIM) can immensely help in solving problems of facility inspection by generating and managing digital representation of the physical and functional characteristics of a facility. This paper describes a model, which is developed to integrate the physical and environmental conditions of a facility on a BIM platform. In this study, factors influencing physical condition and environment condition of the building were identified. Building defects which causes physical deterioration of the building component reduces the ability to perform its intended designed function while environmental condition influences the comfort and health of occupants or users of the building. It is imperative to understand that physical and environment condition of the building are both of vital importance for safety, health and comfort of building users. Factors affecting physical and environment of building were used to develop proposed condition assessment model. Using this proposed model periodic general condition assessment can be performed and correspondingly deterioration graph can be generated for the facility over period of time. Based on inspection data and condition assessment models, building performance can be analyzed for future preventive maintenance.